Growing in generosity? The effects of giving magnitude, target, and audience on the neural signature of giving in adolescence - Suzanne van de Groep; Kiki Zanolie; Sarah M. Burke; Philip Brandner; Andrew J. Fuligni; Eveline A. Crone (Developmental Cognitive Neuroscience, 2022)
Giving is essential for forming and maintaining social relationships, which is an important developmental task for adolescents. This pre-registered fMRI study investigated behavioral and neural correlates of adolescents’ (N = 128, ages 9 – 19 years) small versus large size giving in different social contexts related to target (i.e., giving to a friend or unfamiliar peer) and peer presence (i.e., anonymous versus audience giving). Participants gave more in the small size than large size condition, more to friends than to unfamiliar peers, and more in the audience compared to anonymous condition. Giving very small or large amounts was associated with increased activity in the medial prefrontal cortex (mPFC) and anterior insula (AI), and older adolescents showed increased lateral and anterior PFC activation for small size giving. We observed activity in the intraparietal cortex (IPL), dorsolateral prefrontal cortex, and AI for giving to friends, but no age-related differences in this activity. Behaviorally, in contrast, we observed that older adolescents differentiated more in giving between friends and unfamiliar peers. Finally, we observed interactions between peer presence and target in the AI, and between giving magnitude and target in the precuneus. Together, findings reveal higher context-dependency of giving and more lateral PFC activity for small versus large giving in older adolescents.